MODEL PELESTARIAN MUSIK TRADISI UNTUK KELOMPOK ETNIS DAYAK BAHAU - Putra, Bayu Arsiadhi; Max, J. I. S. D.; Vivian, Y. I. (Buletin Udayana Mengabdi; Vol 19 No 4 (2020): Buletin Udayana Mengabdi, 2020)
Commitment to preserve music from ancestral heritage is increasingly strengthened in ethnic communities that have experienced modern life and migrated to big cities. Unfortunately, various challenges occur outside their control, causing the practice of music to disappear until extinction. Therefore, an understanding of the dangers of the extinction of traditional music, the causal factors and maintenance strategies are needed in the current situation. The activity aims to increase the knowledge and skills of the Dayak Bahau young generation in exploring the challenges and opportunities of traditional music sustainability in the present and the future. Participants are motivated to apply the knowledge they have acquired to examine the threat of the extinction of traditional music in their hometown.